An educational field and its effect on developing the performance of some basic football skills for indoor stadiums (Futsal) - AL-Taie, Haidar Offy Ahmed; Al-Badr, Naji Mutashar Azzat; Almalchy, Najm Abbas Aideem (International Journal of Psychosocial Rehabilitation, 2020)
The study’s importance lies on taking into account the aspects of the sample members and focusing on their weaknesses through designing the educational field and bringing them to the best level of performance of the skills under discussion. The experimental method was used in designing the experimental group with one pre and post-tests, as this study was applied to the players of the football team for indoor Football (Futsal) of the College of Education for Pure Sciences- University of Basra in the academic year (2018-2019) that the number was used is (14) players. Suitable means, tools and tests were used that fit the research requirements, after obtaining the results from the tests, as they were statistically processed using the SPSS. The study came out with conclusions, the most important of which are: The designed educational field has a positive effect in developing the performance of (passing, scoring, trapping, dribbling) football with indoor Football (Futsal) for the individuals in the research sample.